PENGARUH PENGAWASAN, PENGHARGAAN, DAN SANKSI TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR SEKRETARIAT DPRD KABUPATEN LAHAT - Edwar; Marko Ilpiyanto; Nisma Aprini (Ekonomika, 2026)
This study aims to analyze the influence of supervision, rewards, and sanctions on the work discipline of employees at the Secretariat Office of the Lahat Regency DPRD. The research uses a quantitative approach with a survey method through questionnaires. The research population consisted of all 72 employees, and the sampling technique used saturated sampling. Data were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination test with the help of SPSS. The results showed that partially, supervision, rewards, and sanctions have a significant effect on work discipline. Simultaneously, these three independent variables also have a significant effect on work discipline with a coefficient of determination (R²) of 0.767 or 76.7%, while the remaining 23.3% is influenced by other variables outside the study. Sanctions are the variable with the most dominant influence. Based on these findings, it is recommended that management can improve the effectiveness of supervision through a structured system, develop varied performance-based reward systems, and apply sanctions consistently and fairly to enhance and maintain sustainable employee work discipline.